MEMBERDAYAKAN BERPIKIR TINGKAT TINGGI (HIGHER ORDER THINKING) SISWA SMA DALAM PEMBELAJARAN BIOLOGI - I Wayan Karmana (IKIP Mataram, 2013)
The purpose of education in high school biology emphasizes the development of potential students to become independent learners, so that students have the critical thinking skills, creative, innovative, and able to solve the problems of life (higher order thinking). But in reality it is still relatively low ability, so it needs ditingkatkan.Terkait with this, the objective of this study is to clarify the effectiveness of Problem Based Learning (PBL) and potential interaction in the academic as well as empowering high order thinking (critical thinking skills, problem solving, and metacognitive awareness). This is a type of quasi-experimental study that implements two different strategies with pretest-posttest non equivalent control group design 2x2 factorial conducted in academic year 2012/2013. The study population was a tenth grade student at SMAN 8 Mataram, while the study sample were students of class X by 2 classes. The research instrument is a test of critical thinking skills, and problem solving skills, and metacognitive awareness questionnaire. Data were analyzed by descriptive analysis and to test the hypothesis that continued Anacova test further test of Least Significant Difference (LSD). Tally assisted with SPSS 14 for Windows. The results showed that the effect on the Problem Based Learning problem-solving skills, and critical thinking, but do not affect the metacognitive awareness. While the ability (potential) academic has no effect on the ability of problem solving, critical thinking and metacognitive awareness of high school students.